The effect of respiratory muscle training on the maximum oxygen consumption and the anaerobic threshold - Espinosa-Mendez, C. M.; Renero-Carrillo, F. J.; San Martin-Rodriguez, S. L.; Flores-Chico, B. (SportMont, 2020)
The purpose of this research was to determine if respiratory muscle (RM) training, through the MRFit protocol, increases the maximum oxygen consumption and the anaerobic threshold in a group of young professional swimmers, to improve their sports performance. Eleven professional swimmers (7 women and 4 men) between 13 and 17 years old were recruited in this study. Participants were randomly assigned into two groups: control (CG) and training (TG). TG received RM training (MRFit) 20 minutes, two times a week for eight weeks incorporated into their usual training, while the CG only continued their usual training. All the participants performed, before and after the training, ergospirometric tests on a treadmill, to compare the results at the end of the eight weeks. Subsequently, a parametric statistical analysis was performed via a t-test. No significant differences were found for VO2max between CG and TG nor for the anaerobic threshold (p>0.05). Despite the non-significant results, we have determined different tendencies between both groups and clinical improvements.